P4_5 Pandora’s Box - Morris, Owen William; Banks, Lewis Jefferey; Laird, Aaron James; Morris, Liam Stuart (Physics Special Topics, 2021)
In this paper, we aim to investigate the effects of time dilation and how it affects the perception of time on the voyage to Pandora in the well-known franchise Avatar [1]. It was found that the time experienced on the Venture Star Interstellar Spaceship, travelling at a speed of 0.7c [2], was 4.71 years compared to the time experienced on Earth of 6.60 years. This meant that the ageing of the crew was 29% slower than if they had stayed on Earth.